Phleen Pee vocal form in Thai classical music tradition - Orawan Banchongsilpa
The aims of this study were : (1)to describe phleen Pee, a vocal form in the Thai classical music tradition, with particular reference to its vocal melody, (2) to analyze the performance of the phleen Pee by six master singers and (3) to identify present day stylistic features of phleen Pee singing. The study arrived the following findings and conclusions : the components of Phleen Pee are basic melody, a vocal line and a song text.